A wireless bionic soft robotic fish using shape-memory alloy actuators - Ning, Kewei; Sawada, Hideyuki (IAES International Journal of Robotics and Automation (IJRA), 2022)
In this study, we present the construction of a wireless bionic soft robotic fish that has a silicone tail and uses shape-memory alloys (SMAs) as actuators. Even though there have been a lot of recent advancements in the field of soft robotics, the use of SMAs as actuators for soft robots is still not something that is investigated very often. In the course of this research, we plan to work toward the creation of a realistic bionic fish robot that possesses a high level of mobility in the water, in addition to being light enough, strong enough, and flexible enough. The purpose of this study is to expound on the process of optimizing the morphologies of the fish body, as well as the optimization of the electromechanical behavior of the SMAs, in order to generate swimming motions in the fish. Our attention will be on the optimization of these two aspects. This report also outlines some preliminary but promising physical tests that were conducted to create a robotic fish with the similar shape.